2009
DOI: 10.1089/apc.2008.0210
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Medical Treatments and Adherence to Antiretroviral Therapy among HIV-Positive Adults with Histories of Childhood Sexual Abuse

Abstract: HIV is a chronic, life-threatening illness that necessitates regular and consistent medical care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
44
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 59 publications
1
44
0
Order By: Relevance
“…Seven studies (Table 5) describe the impact of SAVA on healthcare utilization and cART adherence among HIV-infected women. [58][59][60][61][62][63][64] Healthcare utilization encompasses ED visits, hospitalizations, adherence to or nonuse of combination antiretroviral therapy (cART) despite medical indication for therapy, attendance at outpatient HIV clinics or nonuse of outpatient services, and use of mental health services. Depending on how healthcare utilization, substance abuse, and interpersonal violence were defined, these studies demonstrated that recent or ongoing IPV has a significant effect on healthcare decision making.…”
Section: Effect Of Sava On Healthcare Utilization and Combination Antmentioning
confidence: 99%
“…Seven studies (Table 5) describe the impact of SAVA on healthcare utilization and cART adherence among HIV-infected women. [58][59][60][61][62][63][64] Healthcare utilization encompasses ED visits, hospitalizations, adherence to or nonuse of combination antiretroviral therapy (cART) despite medical indication for therapy, attendance at outpatient HIV clinics or nonuse of outpatient services, and use of mental health services. Depending on how healthcare utilization, substance abuse, and interpersonal violence were defined, these studies demonstrated that recent or ongoing IPV has a significant effect on healthcare decision making.…”
Section: Effect Of Sava On Healthcare Utilization and Combination Antmentioning
confidence: 99%
“…6 In women with HIV, histories of abuse are quite prevalent, 8,9 and have been linked to risky sexual behaviors, HIV medication nonadherence, antiretroviral failure, and increased mortality. 2,3,8,[10][11][12][13] With highly active antiretroviral therapy (HAART), the HIV infection course has changed to that of a chronic illness. Moderate to high levels of adherence are necessary to achieve viral suppression (i.e., undetectable HIV viral load), reverse immune decline (e.g., improved CD4 + cell count), and decrease risk of morbidity and mortality.…”
mentioning
confidence: 99%
“…[25][26][27][28] A history of trauma or abuse among women with HIV has also been linked significantly to medication nonadherence, 3,11,29 as well as to antiretroviral failure and increased mortality. 2,3,8,11,13 Machtinger and colleagues 3 found that among HIV + biological and transgender women, those who reported recent trauma had over four-times the odds of antiretroviral failure in comparison to HIV + women who did not report recent trauma.…”
mentioning
confidence: 99%
“…[10][11][12] Additionally, among those living with HIV, traumatic stress is associated with medication nonadherence, pain intensity, and interference of pain in daily functioning. [13][14][15] Finally, shame is a common consequence of CSA and has been associated with symptoms of posttraumatic stress disorder (PTSD). [16][17][18][19] Taken together, these findings suggest that the physical and psychological sequelae of CSA contribute to diminished HRQoL among those living with HIV.…”
mentioning
confidence: 99%